Iron Withdrawal with DIBI, a Novel 3-Hydroxypyridin-4-One Chelator Iron-Binding Polymer, Attenuates Macrophage Inflammatory Responses - Javad Ghassemi-Rad; Wasundara Fernando; Bruce E. Holbein; David W. Hoskin (Tabriz University of Medical Sciences, 2023)
Purpose: Iron is an essential trace element for the inflammatory response to infection. In this study, we determined the effect of the recently developed iron-binding polymer DIBI on the synthesis of inflammatory mediators by RAW 264.7 macrophages and bone marrow-derived macrophages (BMDMs) in response to lipopolysaccharide (LPS) stimulation. Methods: Flow cytometry was used to determine the intracellular labile iron pool, reactive oxygen species production, and cell viability. Cytokine production was measured by quantitative reverse transcription polymerase chain reaction and enzyme-linked immunosorbent assay. Nitric oxide synthesis was determined by the Griess assay. Western blotting was used to assess signal transducer and activator of transcription (STAT) phosphorylation. Results: Macrophages cultured in the presence of DIBI exhibited a rapid and significant reduction in their intracellular labile iron pool. DIBI-treated macrophages showed reduced expression of proinflammatory cytokines interferon-β, interleukin (IL)-1β, and IL-6 in response to LPS. In contrast, exposure to DIBI did not affect LPS-induced expression of tumor necrosis factor-α (TNF-α). The inhibitory effect of DIBI on IL-6 synthesis by LPS-stimulated macrophages was lost when exogenous iron in the form of ferric citrate was added to culture, confirming the selectivity of DIBI for iron. DIBI-treated macrophages showed reduced production of reactive oxygen species and nitric oxide following LPS stimulation. DIBI-treated macrophages also showed a reduction in cytokine-induced activation of STAT 1 and 3, which potentiate LPS-induced inflammatory responses. Conclusion: DIBI-mediated iron withdrawal may be able to blunt the excessive inflammatory response by macrophages in conditions such as systemic inflammatory syndrome.